Festive Ukrainian cooking - Farley, Marta Pisetska (Pittsburgh, Pa. : University of Pittsburgh Press, 1990)
Shares menus for traditional Ukrainian feasts and family celebrations, and includes recipes for appetizers, soups, salads, breads, meat, poultry, fish, vegetables, and desserts.
Christmas Eve (Sviata Vechera) -- Christmas (Rizdvo Khrystove) -- Easter (Velykden') -- First sunday after Easter (Provody) -- Feast of Saint George (Sviato Iuriia) -- Pentecost (Zeleni Sviata) -- Feast of Saints Peter and Paul (Petra) -- Feast of the Transfiguration (Spasa) -- Feast of Saint Demetrios (Dmytra) -- Feasts of Saint Catherine and Saint Andrew (Kateryny i Andriia) -- Weddings (Vesillia) -- Name days (Imenyny) -- Gathering wild mushrooms (Hryby).
Includes bibliographical references (pages 207-210) and index.
Print version record.
English.
JSTOR
Keywords: Cooking, Ukrainian; Holiday cooking; Ukraine -- Social life and customs; Cuisine des jours de fête.; COOKING -- General; SOCIAL SCIENCE -- Ethnic Studies -- General; Cooking, Ukrainian; Holiday cooking; Manners and customs; Ukraine; Kookkunst; Cookbook; cookbooks; Cookbooks; Cookbooks; Livres de cuisine